2004
DOI: 10.1017/s0950268803001791
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Streptococcus pneumoniae and Staphylococcus aureus nasopharyngeal colonization in healthy children in the United States

Abstract: This study documents the colonization of Staphylococcus aureus (SA), Streptococcus pneumoniae (SP) and specific resistant forms of these organisms among healthy children and identifies risk factors associated with these pathogens. Prospective point prevalence survey of nasopharyngeal specimens were obtained from 291 healthy children seeking routine well-child care at a university-based ambulatory paediatric clinic in a large urban city in the United States. A total of 291 children less than 5 years were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 22 publications
2
29
2
Order By: Relevance
“…The finding of a prevalence of 41.2% for nasal carriage of S. aureus is higher than those previously reported for children (18.6%-39.2%) [4,10,11]. This might be explained by our highly sensitive culture method, which used a selective enrichment broth.…”
contrasting
confidence: 69%
See 2 more Smart Citations
“…The finding of a prevalence of 41.2% for nasal carriage of S. aureus is higher than those previously reported for children (18.6%-39.2%) [4,10,11]. This might be explained by our highly sensitive culture method, which used a selective enrichment broth.…”
contrasting
confidence: 69%
“…Several studies have aimed to determine the prevalence and risk factors for nasal S. aureus colonization in children and have had variable results [3][4][5][6][7][8]. We aimed to determine the prevalence of and risk factors for nasal S. aureus colonization in children requiring hospitalization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that the nasopharynx and palatine tonsils may be the routes of entry in invasive disease (Madsen et al, 2002). Adhesion of S. suis to mucus in the oral cavity is likely to be important for colonization, as demonstrated for other opportunistic pathogens that colonize the nasopharyngeal cavity (Cheng Immergluck et al, 2004;Faden, 1998;Melles et al, 2007). The demonstration that the apuA : : spc mutant binds less well to porcine gastric mucus is an indication that this surface enzyme may also promote adhesion to mucus in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus carriage rates have been reported in various pediatrics populations in the world ranging from 18.6 to 37.2% (Cheng Immergluck et al 2004;Hussain et al 2001;Kluytmans et al 1997;Wertheim et al 2004). In Turkey, several nasal S. aureus carriage studies have been reported.…”
mentioning
confidence: 99%